Object Orientation in the Literature and in Education - Berges, Marc-Pascal (it - Information Technology, 2018)
The efforts around the world – CS4All in the U.S. or Computing At School in Great Britain – show that computing literacy is seen as important. One important part of computer science education deals with learning programming. So, object orientation should be in focus. But what is object orientation? Several different definitions are presented, and a definition of object orientation by its fundamental concepts is introduced. Furthermore, several educational ``paradigms'' are discussed. Additionally, a choice of object-oriented programming languages is presented. After all that theoretical background, some exemplary implementations of object orientation in national (German) and international curricula are shown. All in all, the article provides a broad overview of the topic of object-oriented programming in computer science education.